2017
DOI: 10.1186/s12893-017-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to airborne particle dispersal in the operating room

Abstract: BackgroundSurgical-site infections due to intraoperative contamination are chiefly ascribable to airborne particles carrying microorganisms. The purpose of this study is to identify the actions that increase the number of airborne particles in the operating room.MethodsTwo surgeons and two surgical nurses performed three patterns of physical movements to mimic intraoperative actions, such as preparing the instrument table, gowning and donning/doffing gloves, and preparing for total knee arthroplasty. The gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Nevertheless, 77% of the deaths following complications from surgery were reported to be related to SSI [ 33 ]. Recent studies have revealed that a large number of airborne particles are produced during typical actions by the surgical staff such as unfolding the surgical gown, removal of gloves and placing arms through the sleeves of the gowns [ 20 ]. Therefore, it can be envisioned that continuous use of far-UVC light during surgical procedures might be an advantageous approach to inactivate bacteria as they alight on the wound [ 1 ], thus preventing infection as well as the formations of bacterial clusters or biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, 77% of the deaths following complications from surgery were reported to be related to SSI [ 33 ]. Recent studies have revealed that a large number of airborne particles are produced during typical actions by the surgical staff such as unfolding the surgical gown, removal of gloves and placing arms through the sleeves of the gowns [ 20 ]. Therefore, it can be envisioned that continuous use of far-UVC light during surgical procedures might be an advantageous approach to inactivate bacteria as they alight on the wound [ 1 ], thus preventing infection as well as the formations of bacterial clusters or biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…To mimic the scenario wherein incisions are infected during surgical procedures as bacteria in the room alight on the skin, we developed a mouse protocol in which MRSA was spread on a defined area of the skin and then exposed to UVC light [ 20 ]. We measured bactericidal efficacy (CFU/g) and effects on skin (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially pathogenic bacteria and moulds were never detected in the surfaces or in the air. The findings of the study are indicative of the efficacy of the cleaning-sanitization procedures adopted, as well as of the appropriate characteristics of the ventilation system which plays a fundamental role in maintaining a low microbial contamination level in operating rooms [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain activities in the OR can increase airborne contaminants. Noguchi et al 22 measured the APC using a laser particle counter during three patterns of physical movement to mimic intraoperative actions during orthopedic surgery. The investigators reported a high APC during the unfolding of the surgical gowns, glove removal, and arm insertion through the sleeves of gowns.…”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%
“…Airborne or aerosolized particles, which can carry microorganisms, can be measured using a counter that reports the air-particulate count (APC), using a microbiologic aircollection device that reports colony-forming units (CFUs), and by culturing the air (eg, with agar plates). [6][7][8]10,[20][21][22][23][24][25][26] Microorganisms that researchers have identified in OR air include Staphylococcus aureus, Staphylococcus epidermidis, Bacillus species, and Streptococcus species. 23 Sources for airborne contaminants can be human skin squames, respiratory aerosols, and dust containing microbial particles.…”
Section: Airborne Sources and Control Of Contaminantsmentioning
confidence: 99%